1982
DOI: 10.1113/jphysiol.1982.sp014294
|View full text |Cite
|
Sign up to set email alerts
|

Control scheme governing concurrently active human motor units during voluntary contractions

Abstract: SUMMARY1. The electrical activity of up to eight concurrently active motor units has been recorded from the human deltoid and first dorsal interosseous muscles. The resulting composite myoelectric signals have been decomposed into their constituent motor-unit action potential trains using a recently developed technique.2. A computer cross-correlation analysis has been performed on motor-unit firing rate and muscle-force output records obtained from both constant-force and triangular force-varying isometric con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
319
7
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(354 citation statements)
references
References 24 publications
21
319
7
4
Order By: Relevance
“…In support of this interpretation, an increase in amplitude and a decrease in median frequency have been found in the contralateral homologous muscle after unilateral muscle fatigue (Morrison et al 2005). Note that common drive refers to a homogeneous input to human MU pools (De Luca et al 1982;De Luca and Erim 1994) and that antagonist cocontraction could be instrumental in maintaining joint stability (Solomonow et al 1988).…”
Section: Discussionmentioning
confidence: 52%
“…In support of this interpretation, an increase in amplitude and a decrease in median frequency have been found in the contralateral homologous muscle after unilateral muscle fatigue (Morrison et al 2005). Note that common drive refers to a homogeneous input to human MU pools (De Luca et al 1982;De Luca and Erim 1994) and that antagonist cocontraction could be instrumental in maintaining joint stability (Solomonow et al 1988).…”
Section: Discussionmentioning
confidence: 52%
“…At the neuromuscular level it has been demonstrated that recruitment of motor units is used during hand force production only up to 40-50% MVC (De Luca et al, 1982;Kukulka and Clamann, 1981), suggesting that rate coding is primarily responsible for increasing force output beyond 50% MVC. Rate coding occurs over a narrower range of forces in older adults (Barry et al, 2007).…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…It was hypothesized that the older adults would require greater levels of activation within these motor areas to achieve the same relative force levels as the younger group. It was expected that these differences would be greatest at higher levels of force production due to the extra neural drive that is needed to overcome the neuromuscular changes that occur with aging (Barry et al, 2007;De Luca et al, 1982;Kukulka and Clamann, 1981). A voxel-wise whole brain analysis was also carried out to determine all of the locations of age-related changes in brain activation during this force modulation task.…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…This phenomenon is often referred to as "short term synchronization" [8] and can be estimated either in the temporal domain using cross-correlation techniques [9] or in the spectral domain by computing coherence functions [10]. The low frequency range in correlation (up to 5 Hz) reflects the usually termed 'common drive' to motor neurons [11] while the range 5-12 is related to the generation of relatively slow movements and tremorogenic oscillations [12]. Higher frequency bands are thought to mainly the interaction between the motor cortex and the spinal pathways [13].…”
Section: Introductionmentioning
confidence: 99%